Unraveling the Crosstalk between Lipids and NADPH Oxidases in Diabetic Kidney Disease - Rachel Njeim; Sahar Alkhansa; Alessia Fornoni (MDPI AG, 2023)
Diabetic kidney disease (DKD) is a serious complication of diabetes mellitus and a leading cause of end-stage renal disease. Abnormal lipid metabolism and intrarenal accumulation of lipids have been shown to be strongly correlated with the development and progression of diabetic kidney disease (DKD). Cholesterol, phospholipids, triglycerides, fatty acids, and sphingolipids are among the lipids that are altered in DKD, and their renal accumulation has been linked to the pathogenesis of the disease. In addition, NADPH oxidase-induced production of reactive oxygen species (ROS) plays a critical role in the development of DKD. Several types of lipids have been found to be tightly linked to NADPH oxidase-induced ROS production. This review aims to explore the interplay between lipids and NADPH oxidases in order to provide new insights into the pathogenesis of DKD and identify more effective targeted therapies for the disease.